1993
DOI: 10.1192/bjp.162.5.621
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Agreement in Psychiatry

Abstract: A random sample of 100 new patients referred consecutively to the psychiatric hospital was assessed using the Arabic translation of the PSE. An abstract form was designed to include all PSE scores as well as the necessary extra data to make ICD-9, ICD-10, and DSM-III-R diagnoses. Kappa correlation was calculated for inter-rater and intra-rater reliability. Overall reliability and reliability of each major psychiatric diagnosis were compared between the three systems. The use of the PSE helped in achieving good… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
1
6
1
Order By: Relevance
“…In one study [17] , the diagnosis of schizoaffective disorder was associated with a low interrater reliability in both DSM-III-R and ICD-10. The results of another study [2] were contradictory in relation to ours: a high kappa value in ICD-10, and a low one in DSM-III-R. Other studies found a high [28] and a reasonable [24] interrater reliability in DSM-IV. In another study [29] , the diagnosis of schizoaffective disorder was associated with a reasonable interrater reliability in ICD-10.…”
Section: Discussioncontrasting
confidence: 52%
See 4 more Smart Citations
“…In one study [17] , the diagnosis of schizoaffective disorder was associated with a low interrater reliability in both DSM-III-R and ICD-10. The results of another study [2] were contradictory in relation to ours: a high kappa value in ICD-10, and a low one in DSM-III-R. Other studies found a high [28] and a reasonable [24] interrater reliability in DSM-IV. In another study [29] , the diagnosis of schizoaffective disorder was associated with a reasonable interrater reliability in ICD-10.…”
Section: Discussioncontrasting
confidence: 52%
“…The higher frequency of diagnosis of schizophrenia according to ICD-10 than DSM-IV or DSM-III-R has also been reported in two additional studies [17,18] , although other studies failed to detect this difference [2,13,[19][20][21] . Indeed, ICD-10 criteria for schizophrenia seem to be less restrictive.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations